Examining the Links Between Child Maltreatment, Risky Behavior, and Adulthood Revictimization: A Life Course Perspective - Wingert, Anne C. (Victims & offenders, 2025)
Child maltreatment can lead to maladaptive coping; therefore, focusing on high-risk behaviors is key to understanding victimization in adulthood. This study examines the extent to which high-risk behaviors mediate between child maltreatment and adulthood victimization using life course theory as a guiding framework. Data from the National Longitudinal Study of Adolescent to Adult Health (N = 14,526) is used for the analysis. The findings underline the salience of child maltreatment as a turning point and high-risk behaviors in maintaining trajectories that lead to later victimization. The mixed mediation findings underscore the nuance surrounding mechanisms fostering victimization across the life course.